2021
DOI: 10.1001/jamapediatrics.2020.5807
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Comorbidity, and Continuity of Psychiatric Disorders in a 15-Year Longitudinal Study of Youths Involved in the Juvenile Justice System

Abstract: IMPORTANCE Previous studies have found that one-half to three-quarters of youths detained in juvenile justice facilities have 1 or more psychiatric disorders. Little is known about the course of their disorders as they age.OBJECTIVE To examine the prevalence, comorbidity, and continuity of 13 psychiatric disorders among youths detained in a juvenile justice facility during the 15 years after detention up to a median age of 31 years, with a focus on sex and racial/ethnic differences. DESIGN, SETTING, AND PARTIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 91 publications
2
29
0
Order By: Relevance
“…Rates of comorbid mental health problems across both study groups were high, consistent with prior studies of justice-involved youth (Teplin et al, 2021; Wasserman et al, 2010). As such, in Family Connect most youth were referred to both mental health and substance use services based on clinical need.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Rates of comorbid mental health problems across both study groups were high, consistent with prior studies of justice-involved youth (Teplin et al, 2021; Wasserman et al, 2010). As such, in Family Connect most youth were referred to both mental health and substance use services based on clinical need.…”
Section: Discussionsupporting
confidence: 85%
“…SUDs are even more common among YIJ: between 25% and 50% report a disorder (McClelland et al, 2004; Teplin et al, 2012, 2021; Yurasek et al, 2021), and an estimated 70% of arrested juveniles have prior drug involvement (Belenko & Logan, 2003; Zhang, 2004). Adolescent SU is a risk factor for SUD in adolescence (Winters & Lee, 2008) and adulthood (Stone et al, 2012), and SU problems in YIJ contribute to their continued involvement with the justice system (Hoeve et al, 2013; Teplin et al, 2021; Wibbelink et al, 2017) as well as other poor outcomes such as HIV/STIs (Elkington et al, 2008), violence (Elkington et al, 2015) and early mortality (Teplin et al, 2014). The well-established overlap between justice involvement and SU, as well as evidence to suggest treatment reduces recidivism in these youth (Cuellar et al, 2004), indicates that identifying and treating their substance use is a crucial public health concern (Cuellar et al, 2004; Henggeler & Sheidow, 2012; Hoeve et al, 2013).…”
mentioning
confidence: 99%
“…Obesity-to-depression and depression-to-obesity pathways have both found empirical support; a recent review found that 80% of community-based longitudinal studies examining obesity-to-depression pathways found evidence for statistical significance, while 53% of those examining depression-to-obesity pathways found evidence for statistical significance [ 18 ]. Parallel to our findings where (69.3%) participants were having mild depression and 60 (10.9%) had moderate depression, Shaffer et al reported that the occurrence of depressive symptoms among children and teenagers aged 9-17 years is estimated to be 5%, while Teplin LA et al stated obesity and overweight are common in teenagers, with over 30% of them being obese [ 19 ].…”
Section: Discussionsupporting
confidence: 84%
“…Substance use disorders, followed by depression and anxiety, are some of the most common mental health issues for juveniles in detention centers (Abram et al , 2003; Wakefield et al , 2019; Wasserman et al , 2010). The 15-year Northwestern Juvenile Project (Teplin et al , 2021) reported that juveniles with existing mental disorders who entered detention still had a mental health disorder after leaving the detention center. Without proper mental health treatment, many of these juveniles will continue to struggle with mental health issues and engage in criminal activity (Ashford and Gallagher, 2019; Barrett and Janopaul-Naylor, 2016).…”
Section: Introductionmentioning
confidence: 99%